Sequential malt lymphomas of the stomach, small intestine, and gall bladder. Issue 1 (January 1998) - Stephen, M R; Farquharson, M A; Sharp, R A; Jackson, R
Abstract : Low grade lymphomas of mucosa associated lymphoid tissue (MALT) are indolent neoplasms that, although tending to remain localised for many years, may spread to other mucosal sites. A 53 year old woman treated by total gastrectomy for low grade MALT lymphoma of the stomach developed a recurrence in the small bowel 18 years later, and a further recurrence involving the gall bladder after three years in complete clinical remission after chemotherapy. In situ hybridisation showed that the small intestine and gall bladder recurrences had the same pattern of light chain restriction. Tumour from all three sites was shown to be derived from a single clone by the demonstration of an identical immunoglobulin heavy chain gene rearrangement by the polymerase chain reaction. The case illustrates the propensity of MALT lymphomas to "home" to mucosal sites and gives an insight into their behavior over an extended follow up.